2019
DOI: 10.1089/env.2019.0008
|View full text |Cite
|
Sign up to set email alerts
|

Socioecological Production of Parks in Atlanta, Georgia's Proctor Creek Watershed: Creating Ecosystem Services or Negative Externalities?

Abstract: For decades, grassroots activists have engaged in efforts to resurrect the integrity of Atlanta, Georgia's Proctor Creek Watershed, by creating a narrative about the value of the ecological and sociohistorical worth of the watershed. These efforts have resulted in both small-and large-scale adaptive reuse green space projects in Proctor Creek, intended to mitigate flooding and to provide recreational opportunities for socially disadvantaged residents. This kind of place making is consistent with Henrik Ernstso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Few studies directly compared how the function and/or quality of different types of greening may influence gentrification (but see recent work by Amorim Maia et al, 2020; Chen et al, 2021; Kim and Wu, 2021; Pearsall and Eller, 2020; Rigolon and Németh, 2020) although many earlier studies made inferences about it (e.g., Anguelovski et al, 2017; Johnson Gaither, 2019). Although this study focused on vegetative greening, some papers also discussed other types of greening alongside vegetation, such as LEED-certified buildings (Checker, 2011; Yazar et al, 2020), cycle lanes (Goodling et al, 2015; Ali et al, 2020), and public transit (Quastel, 2009; Rigolon et al, 2020b), highlighting the link between vegetative and non-vegetative drivers of green gentrification.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies directly compared how the function and/or quality of different types of greening may influence gentrification (but see recent work by Amorim Maia et al, 2020; Chen et al, 2021; Kim and Wu, 2021; Pearsall and Eller, 2020; Rigolon and Németh, 2020) although many earlier studies made inferences about it (e.g., Anguelovski et al, 2017; Johnson Gaither, 2019). Although this study focused on vegetative greening, some papers also discussed other types of greening alongside vegetation, such as LEED-certified buildings (Checker, 2011; Yazar et al, 2020), cycle lanes (Goodling et al, 2015; Ali et al, 2020), and public transit (Quastel, 2009; Rigolon et al, 2020b), highlighting the link between vegetative and non-vegetative drivers of green gentrification.…”
Section: Resultsmentioning
confidence: 99%
“…Real estate markets have improved significantly across the US in recent years, including in the City of Atlanta. As well, large, green infrastructure projects are drawing wealthier, white people to south and westside Atlanta neighborhoods (Immergluck & Balan, 2017;Johnson Gaither, 2019). There has been a concomitant criticism of these trends, but some amount gentrification is inevitable and is already evident in west Atlanta.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies (Gilstad-Hayden et al, 2015;Troy et al, 2012;Troy et al, 2016;Wolfe & Mennis, 2012), we argue that people's participation in and with greenspace is a crucial factor in this relationship. This interaction can occur when greenspace serves as a physical location for positive, social interaction or when humans are motivated to care for and protect both mundane, urban open spaces, and those of particular socioecological significance (Ernstson, 2013;Johnson Gaither, 2019;Locke et al, 2016;Murphy-Dunning, 2009). For instance, in the University of Illinois's series of studies on resident responses to greenspace in Chicago housing projects, findings indicated that crime rates for both property and violent crimes were lower around buildings with more trees.…”
Section: Trees and Trash: Examining The Link Introductionmentioning
confidence: 99%
“…While Atlanta was the only city in the archipelago that built a combined sewer system (serving the city limits as defined in 1910), its overflows have repeatedly degraded water quality in the Chattahoochee River and reduced assimilative capacity for downstream municipalities. Flooding events associated with CSOs have threatened the health and safety of the residents of Atlanta, and have been most prevalent in non‐White and impoverished communities (Johnson Gaither, 2019). Recently, Atlanta greatly reduced its combined sewer overflow problems by (1) separating storm and sanitary sewers over about 27% of the combined network, and (2) building 18.5 miles of 30‐foot diameter CSO storage tunnels under the city at an approximate cost of $3B (EPA Office of Inspector General, 2018).…”
Section: Water Quality and Aquatic Ecosystemsmentioning
confidence: 99%
“…The tunnels store a large proportion of CSO flows during storms, so they can be treated between storms. However, the city has yet to mitigate the effects of all combined systems, and some regions of the city, such as the Entrenchment Creek, South River, and Proctor Creek Watersheds, still regularly experience CSO-associated flooding and water quality problems geographically coincident with low-income non-White neighborhoods (Deme, 2021;Entrenchment Creek One Water Management Task Force, 2020;Johnson Gaither, 2019).…”
Section: Water Qualit Y and Aquati C Ecosys Temsmentioning
confidence: 99%